Determinants of epilepsy treatment gap : place of the quality of antiepileptic drugs in sub-Saharan Africa - (:unkn) unknown (My University, 2018)
In sub-Saharan Africa, epilepsy remains a neglected public health issue. In addition to a lack of trained healthcare resources, including staff and infrastructure, the high epilepsy treatment gap has been a source of concern. Only a few major first-line antiepileptic drugs are readily available and the quality of these drugs could pose further issues. Currently, there are a few data available to address the question of the quality of antiepileptic drugs in low- and middle-income countries. Two studies have shown the proportion of poor-quality drugs to range from 13.7% for phenobarbital in Mauritania to 65,0% for phenytoin, carbamazepine, and sodium valproate in Vietnam. The aim of this study was to assess the determinants of the treatment gap of people living with epilepsy in low- and middle-income countries. Research objectives were to identify and describe intervention programmes aimed at improving drug management, to extract social determinants of the treatment gap, to evaluate the quality of antiepileptic drugs available in sub-Saharan Africa and to measure the availability, cost and affordability of antiepileptic drugs in sub-Saharan Africa.The study design for intervention and social determinants assessment was a systematic literature review. For quality, availability, cost and affordability issues a multicentre cross-sectional study has been carried out in 9 sub-Saharan Africa countries with an identical data and sample collection protocol. In each country, urban and rural areas have been systematically investigated in the same manner, exploring both the official supply chain and the illicit system in each setting. All the structures where a patient could buy or obtain antiepileptic drugs have been investigated. Community-based care and allied health staff were success factors in resource limited settings. Adherence to treatment has been pointed out to be a corner stone of people living with epilepsy drug management, poorly and slightly controll
Keywords: African Research